2008
DOI: 10.1177/070674370805300903
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Repetitive Transcranial Magnetic Stimulation Use in the Treatment of Schizophrenia

Abstract: D eveloped for various investigative and potential therapeutic purposes, rTMS is a relatively new technique. Its use in experimental settings is growing rapidly 1 and its potential as a treatment is being tested in numerous neurological and psychiatric conditions. Most research and interest has focused on the potential application of rTMS in the treatment of depression. In addition, in recent years an increasing number of open and double-blind studies of rTMS were conducted in patients with schizophrenia. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 74 publications
1
20
0
2
Order By: Relevance
“…For example, rTMS has been shown to alter the RMT and decrease MEP size. 82 Further to these local effects, there are related plastic changes found in interconnected brain regions after the application of rTMS trains. 82 Therefore, rTMS activation of the motor system can be used to study brain plastic processes in vivo.…”
Section: Repetitive Tmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, rTMS has been shown to alter the RMT and decrease MEP size. 82 Further to these local effects, there are related plastic changes found in interconnected brain regions after the application of rTMS trains. 82 Therefore, rTMS activation of the motor system can be used to study brain plastic processes in vivo.…”
Section: Repetitive Tmsmentioning
confidence: 99%
“…82 Further to these local effects, there are related plastic changes found in interconnected brain regions after the application of rTMS trains. 82 Therefore, rTMS activation of the motor system can be used to study brain plastic processes in vivo. Oxley et al 83 investigated changes in motor cortex excitability following rTMS applied over the premotor cortex in patients with schizophrenia.…”
Section: Repetitive Tmsmentioning
confidence: 99%
“…For instance, in a sham-controlled study, Mittrach et al [83] investigated the tolerability and safety of 10-Hz rTMS over the left Dorsolateral Prefrontal Cortex (DLPFC) with respect to cognitive functions and did not observe deterioration of cognitive functions. In addition, the comprehensive review of Fitzgerald and Daskalakis [84] showed that there is no consensus about whether rTMS could play a role in reducing the negative symptoms of schizophrenia when applied over these areas.…”
Section: Schizophreniamentioning
confidence: 99%
“…Bioengineers are currently examining ways to retrofit existing TMS apparatus to simulate its artifacts so as to improve testing validity [147,148]. The sham condition poses the same problems for validating effectiveness in treating other conditions as well, including bipolar disorder [149], schizophrenia [150], obsessive-compulsive disorder [151], post-traumatic stress disorder [152] and stroke [153]. Nevertheless, the enthusiasm for this technology, largely due to its non-invasiveness, intuitive plausibility, and ability to trigger direct effects in the brain, remains high even if the possibility of elucidating its mechanism of action will most likely remain a mystery for some time to come.…”
Section: Brain Machine Interface (Bmi)mentioning
confidence: 99%